Effect of micro double helical grooved tools on performance of electric discharge drilling of Ti-6Al-4V. (September 2021) - Jacob, Krupa Serah; Samuel, G.L.
Machining of complex features and holes on superalloys is a topic of both industrial and academic interest. Though the demand for high aspect ratio holes on Ti-6Al-4V is high in aerospace, biomedical and chemical industries, machining the same is very challenging due to the low thermal conductivity and debris accumulation in the machining zone. The present-day methods of hole drilling by unconventional methods like Electric Discharge Machining (EDM) make use of electrodes with poor flushing capabilities. Hence the motivation of the present work is to develop a method to modify the geometry of Electric Discharge Drilling (EDD) tools in order to enhance debris removal. For the first time an attempt has been made to machine micro double-helical grooves on EDD tools in a single pass. Solid, single-helical and double-helical electrodes are developed and through-holes are drilled on a Ti-6Al-4V workpiece. A comparative analysis of the performance of these three types of tools with respect to the machining time, electrode wear rate and hole quality is carried out. From Computational Fluid Dynamics (CFD) simulations it is seen that the double-helical grooved tool is superior in debris removal. The best values of the machining time of 183.33 s, overcut of 2.19 mm, hole taper angle of 7.93° and area of recast layer of 6.66 mm 2 are obtained on the holes machined using double-helical electrodes. The mentioned tool has the potential to overcome the problem of debris removal in high aspect ratio hole drilling and surpass the present-day electric discharge drilling tools.